The Inheritance of Dzawil Arham According to Imam Syafi'i in The View of Maqashid Syari'ah - Zul Atril; Zulkifli; Muliyadi Thaib, M. A (UIN Mahmud Yunus Batusangkar, 2026)
Divergent views on the inheritance rights of dhawu al-arham (distant kindred) remain a significant issue in Islamic inheritance law, particularly regarding Imam Shafi'i's position, which excludes them from inheritance even in the absence of dhawu al-furudh (fixed-share heirs) and ashabah (residuary heirs). This study analyzes Imam Shafi'i's perspective and evaluates it through the framework of maqasid al-shari'ah. Employing library research with a qualitative analytical approach, the study uses classical Shafi'i legal texts as primary sources and contemporary books and scholarly articles as secondary sources. The findings show that inheritance rights are limited to dhawu al-furudh and ashabah, based on legally recognized causes of inheritance: lineage (nasab), marriage, and al-wala' (patronage). Because no explicit Sharia text assigns a share to dhawu al-arham, they are excluded from inheritance. When no eligible heirs exist, the estate is transferred to the Baitul Mal (public treasury) for public benefit. From the perspective of maqasid al-shari'ah, Imam Shafi'i's view upholds the protection of wealth (hifzh al-mal), legal certainty, and the prevention of harm through adherence to established Sharia principles. contemporary public sphere, rather than viewing it merely as an administrative issue in the halal certification process.